Penyuluhan Pencegahan Gizi Buruk dalam Upaya Peningkatan Kualitas Kesehatan pada Peserta Didik: (Sekolah Dasar Negeri 101848 Desa Kuala Lau Bekeri Kecamatan Kutalimbaru) - Heppy Jelita Sari Batubara; Sukma Febriani; Cherry Permata Putri; Hazrati Hazrati; Marni Nadratul Jannah; M. Salsabil Yasjudan Noor Nasution (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Personal hygiene and nutritional balance are very important for everyone to know, including children during their most critical growth period, to know. This Community Service Lecture (KKN) activity aims to increase the knowledge and awareness of students at Public Elementary School 101848, Kuala Lau Bekeri Village, Kutalimbaru District, regarding the prevention of malnutrition and self hygiene through educational counseling. The method used was a descriptive method with a qualitative approach, implemented through interactive lectures, presentation media, and question and answer sessions. The number of participants were 90 students from grades I to VI. And with the teachers support in maintaining regularity and reinforcing the educational presentation about the counseling material included the definition of nutrition and malnutrition, signs, causes, healthy eating patterns, and clean and healthy living behaviors. The results of the activity showed high enthusiasm from the participants in participating in the counseling and their ability to name examples of healthy foods and the importance of a healthy lifestyle. This counseling successfully increased participants' understanding of the importance of balanced nutrition and healthy living behaviors that play a role in supporting the optimal growth and development of school-age children. The involvement of teachers and schools greatly supported the success of this activity. It is hoped that this counseling can form positive habits in maintaining students' nutrition and health in a sustainable manner.